Spherical particles of pure and manganese doped zinc oxide and zinc hydroxicarbonate - Zampronio, Cleidiane G. [UNESP]; Davolos, Marian R. [UNESP]; Stucchi, Elizabeth B. [UNESP]; Jafelicci, Miguel [UNESP] (My University, 1995)
Pure and manganese doped zinc hydroxicarbonate are precursors for materials based on zinc oxide with electrical and luminescent properties. This paper reports on investigation of the effect of chloride and sulfate anions in the morphology of pure and doped precursors obtained by aging diluted zinc salt solutions in presence of urea, and their thermally decomposed products. Characterization was carried out by XRD, IR and SEM techniques. Hydrozincite Zn5(OH)6(CO3)2 and zincite ZnO with spherical shaped particles of 5-10 μm were obtained independent of anion used. Moreover, in a chloride medium the spheres are organized in an arrangement of acicularly crystallized units as spherulitic aggregates, and in sulfate medium porous spherical particles were observed. In addition, there is a good topotaxic relationship between the precursor and oxide.